2010
DOI: 10.1103/physrevlett.105.174501
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Composite Nanochannels as Nanopumps Driven by Symmetric Temperature Gradients

Abstract: In this Letter, we propose a composite nanochannel system, where half of the channel is of low surface energy, while the other half has a relatively high surface energy. Molecular dynamics simulations show that fluids in such channels can be continuously driven by a symmetric temperature gradient. In the low surface energy part, the fluid moves from high to low temperature, while the fluid migrates from low to high temperature in the high surface energy part. The mechanisms that govern the flow are explained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 22 publications
1
44
1
Order By: Relevance
“…1,3,24 Recently, we studied nanochannel flows and found that the coupling of temperature and surface effects could lead to different flow fashions. 4,25 We have numerically demonstrated that a fluid can be continuously circulated by a symmetric temperature gradient in nanochannels of heterogeneous surface energies. This fluid transport mechanism can be employed for thermal management by using the waste heat generated by chips/devices instead of external forces.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,24 Recently, we studied nanochannel flows and found that the coupling of temperature and surface effects could lead to different flow fashions. 4,25 We have numerically demonstrated that a fluid can be continuously circulated by a symmetric temperature gradient in nanochannels of heterogeneous surface energies. This fluid transport mechanism can be employed for thermal management by using the waste heat generated by chips/devices instead of external forces.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to externally induce the movement and directly study the motion of model nanodroplets in contact with substrate interface may provide an insight to dynamic properties of interfacial water by experimentally complementing theoretical simulations. Such studies will be critical in the design of materials tailored to the adhesion and flow of liquids at the interface (20,21).…”
mentioning
confidence: 99%
“…This means that drug molecules dissolved in a water droplet and can be delivered to a target area along the CNTs. Previous works have shown that the boundary condition is a critical issue in nanoscale systems [29,30]. Hummer et al [31] and Wu et al [32] have shown that a minute change in the attraction between the tube wall and water can dramatically affect pore hydration, leading to a sharp transition between empty and filled states within a nanosecond time scale.…”
Section: Introductionmentioning
confidence: 99%